The effect of immersion acrylic resin artificial teeth in basil leaves extract on color changes - Amanda, Belia Putri; Wahyuni, Siti (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Acrylic resin artificial teeth are a substitute for natural teeth that have been lost and are the most important component of dentures in restoring aesthetic, masticatory and phonetic functions. Denture cleansers made from chemicals can affect the mechanical and physical properties of acrylic resin. Natural denture cleansers are used as an alternative to minimize the effects caused by chemical denture cleansers. 12.5% basil leaves extract was used as an alternative denture cleansers. This study  aimed to analyse the effect of immersing acrylic resin artificial teeth in 12.5% basil leaves extract and alkaline peroxide for 5 days on color changes. Methods: This research was an experimental laboratory. The samples used were 30 maxillary central incisor acrylic resin artificial teeth 20x20x6mm divided into 3 immersion groups: in 12.5% basil leaves extract; alkaline peroxide; and aquabides. The color change of the sample was measured using colorimeter at the  labial surface of the artificial teeth. The results of the data were analyzed by One-way Anova and continued with LSD test. Results: The mean value of color change acrylic resin artificial teeth after immersion in 12.5% basil leaves extract for 5 days = ∆E 1,86±0,17, alkaline peroxide = ∆E 3,48±0,21, and aquabides = ∆E 1,20±0,15  with a value of p=0.0001(p<0.05). Conclusion: There was an effect of immersing artificial teeth in acrylic resin in 12.5% basil leaves extract and alkaline peroxide for 5 days on discoloration. 12.5% basil leaves extract can be used as an alternative denture cleansers because the discoloration that occur were still within the standard range of color changes.KEY WORDS: acrylic resin artificial teeth; basil leaves extrac; color changesPengaruh perendaman gigi artifisial resin akrilik dalam ekstrak daun kemangi terhadap perubahan warnaABSTRAKPendahuluan: Gigi artifisial resin akrilik adalah pengganti gigi asli yang telah hilang dan merupakan komponen terpenting dari gigi tiruan dalam memulihkan fungsi estetis, mastikasi dan fonetik. Pembersih gigi tiruan berbahan kimia dapat memengaruhi sifat mekanis dan fisik resin akrilik. Pembersih gigi tiruan alami digunakan sebagai alternatif untuk meminimalkan efek yang ditimbulkan oleh pembersih gigi tiruan berbahan kimia. Ekstrak daun kemangi 12,5% digunakan sebagai alternatif bahan pembersih gigi tiruan. Tujuan penelitian menganalisis pengaruh perendaman gigi artifisial resin akrilik dalam ekstrak daun kemangi 12,5% dan alkalin peroksida selama 5 hari terhadap perubahan warna. Metode: Jenis penelitian eksperimental laboratoris. Sampel yang digunakan adalah 30 gigi artifisial resin akrilik insisivus sentral rahang atas untuk diuji dengan ukuran sampel 20x20x6mm dibagi 3 kelompok perendaman yaitu perendaman dalam ekstrak daun kemangi 12,5%; alkalin peroksida; aquabides. Perubahan warna diukur menggunakan colorimeter pada permukaan labial gigi artifisial. Hasil data dianalisis dengan uji One-way Anova dan dilanjutkan dengan uji LSD Hasil: Nilai rerata perubahan warna gigi artifisial resin akrilik setelah direndam dalam ekstrak daun kemangi 12,5% selama 5 hari = ∆E 1,86±0,17, alkalin peroksida = ∆E 3,48±0,21 ,dan aquades = ∆E 1,20±0,15 dengan nilai p=0,0001(p<0,05). Simpulan: Terdapat pengaruh perendaman gigi artifisial resin akrilik dalam ekstrak daun kemangi 12,5% dan alkalin peroksida selama 5 hari terhadap perubahan warna. Ekstrak daun kemangi 12,5% dapat digunakan sebagai bahan alternatif pembersih gigi tiruan karena perubahan warna yang terjadi masih dalam rentang nilai yang diterima secara klinis pada resin akrilik.KATA KUNCI: gigi artifisial resin akrilik;ekstrak kemangi;perubahan warna.